2016
DOI: 10.1111/jpn.12460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dystocia on subsequent reproductive performance and functional longevity in Holstein cows

Abstract: The objective of this study was to evaluate the effect of dystocia on the reproductive performance and functional longevity in Iranian Holsteins. Data consisted of 1 467 064 lactation records of 581 421 Holstein cows from 3083 herds which were collected by the Animal Breeding Center of Iran from April 1987 to February 2014. Reproduction traits in this study included interval from first to second calving, days open and days from first calving to first service. The generalized linear model was used for the stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
(90 reference statements)
0
6
0
3
Order By: Relevance
“…Calving ease significantly reduces the service life and reproductive performance of dairy cows ( Maturana et al, 2007 ). Although the criteria for calving difficulty vary from country to country, the result is that unassisted cows live longer than cows that require assistance during delivery ( Hossein-Zadeh, 2016 ). Dystocia reduces herd profitability, impairs the reproductive performance of cows in the next breeding cycle, and reduces milk production ( Hossein-Zadeh, 2016 ).…”
Section: Longevity With Other Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calving ease significantly reduces the service life and reproductive performance of dairy cows ( Maturana et al, 2007 ). Although the criteria for calving difficulty vary from country to country, the result is that unassisted cows live longer than cows that require assistance during delivery ( Hossein-Zadeh, 2016 ). Dystocia reduces herd profitability, impairs the reproductive performance of cows in the next breeding cycle, and reduces milk production ( Hossein-Zadeh, 2016 ).…”
Section: Longevity With Other Traitsmentioning
confidence: 99%
“…Although the criteria for calving difficulty vary from country to country, the result is that unassisted cows live longer than cows that require assistance during delivery ( Hossein-Zadeh, 2016 ). Dystocia reduces herd profitability, impairs the reproductive performance of cows in the next breeding cycle, and reduces milk production ( Hossein-Zadeh, 2016 ). Rajala-Schultz and Gröhn (1999) found that the risk of culling for dystocic cows was significantly increased during the first 30 days after calving and at the end of the lactation.…”
Section: Longevity With Other Traitsmentioning
confidence: 99%
“…9 One study into the fate of dairy cows after difficult calvings described that 10% of cows that died had "serious difficulties" at calving, 6 whereas another described culling rates in Holstein cows as being increased with an increase in calving assistance score. 56 This study focused on live calves that were delivered per vaginum. It was striking that nearly one in five calves (17.8%) required assistance at calving, which is likely an underestimate of the true rate of dystocia in GB spring born suckler calves, given that Caesarean T A B L E 3 GLMM multivariable mixed logistic model 2 outputs, with fixed effect variables, number of calves (n), number of calves requiring assistance at calving (nAssist), p-values, and odds ratios (including 95% confidence intervals in brackets) sections and calves that died are not included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…There are also additional welfare considerations relating to pain and discomfort for both the cow and calf. Increased time open after calving (an increase from slight to serious difficulty in calving increased days open from 9.2 to 21.5 days 6 ), decreased pregnancy rates 9,56 and decreased milk production 9,57 are all reported in dairy cows, while poor conception rates and reduced oestrus expression in beef cows post dystocia have also been reported 3 . Dystocia also results in increased loss of bodyweight and condition in affected Holstein‐Friesian cows 9 .…”
Section: | Discussionmentioning
confidence: 99%
See 1 more Smart Citation